2010
DOI: 10.1021/es9029864
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FTIR and Particle Mass Spectrometry for the Measurement of Particulate Organic Nitrates

Abstract: While multifunctional organic nitrates are formed during the atmospheric oxidation of volatile organic compounds, relatively little is known about their signatures in particle mass spectrometers. High resolution time-of-flight aerosol mass spectrometry (HR-ToF-AMS) and FTIR spectroscopy on particles impacted on ZnSe windows were applied to NH(4)NO(3), NaNO(3), and isosorbide 5-mononitrate (IMN) particles, and to secondary organic aerosol (SOA) from NO(3) radical reactions at 22 degrees C and 1 atm in air with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
166
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(189 citation statements)
references
References 69 publications
17
166
6
Order By: Relevance
“…Several studies show that qualitative measurements and quantification of organic nitrates are of major interest (e.g., Fry et al, 2009;Bruns et al, 2010;Farmer et al, 2010;Ayres et al, 2015;Kiendler-Scharr et al, 2016;Liu et al, 2017;Schneider et al, 2017). Organic nitrates are decomposed during the evaporation and/or ionisation processes in the C-ToF-AMS and, therefore,…”
Section: Particulate Organic Nitratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies show that qualitative measurements and quantification of organic nitrates are of major interest (e.g., Fry et al, 2009;Bruns et al, 2010;Farmer et al, 2010;Ayres et al, 2015;Kiendler-Scharr et al, 2016;Liu et al, 2017;Schneider et al, 2017). Organic nitrates are decomposed during the evaporation and/or ionisation processes in the C-ToF-AMS and, therefore,…”
Section: Particulate Organic Nitratesmentioning
confidence: 99%
“…Many studies reported on the difficulties to measure organic 10 nitrates quantitatively, but suggested also a possibility to estimate the amount or at least the presence of organic nitrates based on the measured ion ratios of NO + to NO + 2 using aerosol mass spectrometry (e.g., Bruns et al, 2010;Farmer et al, 2010;Rollins et al, 2010;Fry et al, 2013;Ayres et al, 2015;Kiendler-Scharr et al, 2016;Ng et al, 2017;Schneider et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2)(3)(4)(5)(6)) and chemical ionization mass spectrometry (7)(8)(9), and the total of gas and aerosol RONO 2 (total Alkyl Nitrates, ΣAN) has been observed by Thermal Dissociation Laser Induced Fluorescence (TD-LIF) (1,(10)(11)(12). Recently there has been growing interest in understanding the partitioning of RONO 2 to atmospheric particles (13)(14)(15)(16)(17)(18). RONO 2 molecules with 2 -4 functional groups and a carbon backbone of ≥ C 4 have low enough vapor pressures to condense under ambient conditions and mechanistic studies show that RONO 2 can be among the most important molecules to SOA formation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However the most widely used methods for aerosol chemical characterization including Aerosol Mass Spectrometry (AMS) have had limited success. The difficulty of distinguishing inorganic and organic nitrates using AMS has been recently discussed in the literature (16)(17)(18). Nitrates have not yet been reported by Thermal Desorption Aerosol Gas-Chromatography (TAG) (25) or other methods of detailed realtime aerosol characterization.…”
Section: Introductionmentioning
confidence: 99%